Declines in occurrence of plants characteristic for a nutrient‐poor meadow habitat are partly explained by their responses to nutrient addition and competition - Höckendorff, Stefanie (Ecol Evol, 2021)
Species losses and local extinctions are alarmingly common, frequently as a consequence of habitat destruction. Nevertheless, many intact habitats also face species losses, most likely due to environmental changes. However, the exact drivers, and why they affect some species more than others in apparently intact habitats, are still poorly understood. Addressing these questions requires data on changes in occurrence frequency of many species, and comparisons of the responses of those species to experimental manipulations of the environment. Here, we use historic (1911) and contemporary (2017) data on the presence–absence of 42 plant species in 14 seemingly intact Molinia meadows around Lower Lake Constance to quantify changes in occurrence frequency. Then, we performed a common‐garden experiment to test whether occurrence frequencies in 1911 and changes therein by 2017 could be explained by responses of the 42 species to nutrient addition and competition with the acquisitive generalist grass Poa pratensis. Within the 14 still intact Molinia meadows, 36 of the 42 species had declined since 1911. As expected, nutrient addition generally led to increased biomass production of the 42 target species, and competition with P. pratensis had a negative effect. The latter was stronger at high nutrient availability. The more frequent species were in 1911 and the more they declined in frequency between 1911 and 2017, the less above‐ground biomass they produced in our experiment. Competition with P. pratensis magnified this effect. Our work highlights that environmental change can contribute to local extinction of species in otherwise intact habitat remnants. Specifically, we showed that increased nutrient availability negatively affected formerly widespread Molinia‐meadow species in competition with P. pratensis. Our study thus identified a likely mechanism for the decline in occurrence frequency of species in the remaining Molinia meadows.